Integrated Evaluation and Learning System with OBE Ecosystem and “MBKM” - I Gede Susrama Mas Diyasa; I Nyoman Dita Pahang Putra; Ni Made Ika Marini Mandenni; Mohammad Rafka Mahendra Ariefwan; Rangga Laksana Aryananda (Nusantara Science and Technology Proceedings, 2022)
Outcome-Based Education (OBE) is an outcome-based or achievement-based learning system. The system emphasizes the achievements of student learning that must be identified first (for example, students must have the attainment of knowledge about something that must be mastered or students must have skills that must be achieved, for example, having to know knowledge about websites and having to be able to make webs) which can then be used as a basis for determining the future, planning what learning methods are, and assessments (assignments, quizzes, presentations, tests, etc.) adjusted to these outputs (results of statistical analysis of previous results/outcomes). In contrast to traditional learning, the major attention is on the teaching and learning process that adapts to the material in the syllabus. In addition, the assessment in conventional learning uses the knowledge that must be achieved, while the OBE assessment process uses a predetermined outcome level. The outcome to be determined and achieved is determined based on the stakeholder (alumni, graduate, company/workplace, or someone who has an interest and is bound by the study program or course that adapts to the needs of the company or workplace), if traditional learning only uses the syllabus or material that has been determined which is relatively the same every year.